Disability pension receipt in young adults: an analysis of the Swiss Social protection and labour market (SESAM) data - Szilvia Altwicker-Hámori; Julia Dratva (BMC, 2019)
Abstract Background There has been an overall decreasing trend in the inflow into disability pension in Switzerland since 2003 with the exception of young adults. Disablement in young adulthood reflects a particularly critical phenomenon given the potentially far-reaching long-term social, economic and health consequences. The aim of this study was therefore to identify factors for disability pension in young adults aged 18-39, living in Switzerland. Methods We used the 2010-2015 cross-sections of the Social protection and labour market; a unique dataset linking microdata from the Swiss Labour Force Survey, the Swiss Central Compensation Office Register, and the Unemployment Insurance Register. Multiple logistic regression was employed to explore the association between demographic, socioeconomic, and health factors and disability pension in young adults living in Switzerland with long-term activity limitation (N = 5306). Alternative specifications of the benchmark model were estimated as robustness checks; and subsample analyses were conducted excluding (i) those aged 18-24 and (ii) those with partial disability pension. Results Our regression results showed that those living without a working partner (OR 2.11; 95% CI 1.51-2.94) and without a child aged 0-14 (OR 2.15; 95% CI 1.48-3.12), born in Switzerland (OR 2.68; 95% CI 1.87-3.84), of higher age (OR 1.16; 95% CI 1.12-1.19), having completed at most lower secondary school (OR 3.26; 95% CI 2.24-4.76), lacking income throughout the four-year period prior to interview (OR 3.94; 95% CI 2.70-5.75), suffering from chronic illness (OR 4.52; 95% CI 2.83-7.19), and severe long-term activity limitation (OR 4.52; 95% CI 2.83-7.19) had higher odds of DP. Our findings were robust to alternative specifications and subsamples; and the alternative specifications revealed differences by learnt occupation, with highest odds for those without an occupational qualification (OR 5.93; 95% CI 3.72-9.46; p-value 0.000) and for those in 'Manufacturing' (OR 3.59; 95% CI 1.91-6.71) relative to 'Health, education, culture, and science'. Conclusions Most importantly, our results showed that educational and employment factors are of high relevance, as well as chronic morbidity and severe long-term activity limitation. From a policy perspective, early intervention should thus focus on the attainment of vocational and academic qualifications beyond the lower secondary level, facilitating school-to-work transition and labour market integration.